ANALYSIS OF THE INFLUENCE OF QUALITY OF WORK LIFE, TRANSFORMATIONAL LEADERSHIP AND EMPLOYEE COMPETENCE ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE WELL BEING CASE STUDY AT PT. PLAZA AUTO RAYA - Nuradi Mulya Razaq; Ida Aju Brahmasari, Ida Aju Brahma Ratih (Adisam Publisher, 2025)
In the Company, Human Resources are needed to meet the Company's success goals, because Human Resources (Human Resources) is one of the valuable assets that are able to overcome various problems as part of the work in supporting the company's activities. In the world of work, HR (Human Resources) must have effective and efficient performance to get results from work performance so that the company must be able to manage human resources well and maintain the performance of its best employees who have high competence towards the company. Employee performance itself can affect factors including superior leadership style, relationships between employees, and quality of work life. The author's goal is to find out the influences: Quality of Work Life, Transformational Leadership and Competence on Employee Performance Through Employee Wellbeing Case Study on PT. Plaza Auto Raya. The sample taken was 100 people. The data analysis technique uses the Structural Equation Modeling method with the results of this study (1) There is a positive influence of Quality of Work Life on Employee Performance, (2) There is no positive influence of Transformational Leadership on Employee Performance, (3) There is a positive influence of Employee Competence on Employee Performance, (4) There is a positive influence of Employee Well-Being on Employee Performance, (5) There is no positive influence of Quality of Work Life on Employee Well-Being, (6) There is no positive influence of Transformational Leadership on Employee Well- Being, (7) There is a positive influence of Employee Competence on Employee Well- Being.